Distributed Leadership - Spillane, James P. (Jossey-Bass, 2006)
James Spillane, the leading expert in Distributed Leadership, shows how leadership happens in everyday practices in schools, through formal routines and informal interactions. He examines the distribution of leadership among administrators, specialists, and teachers in the school, and explains the ways in which leadership practice is stretched over leaders, followers, and aspects of the situation, including routines and tools of various sorts in the organization such as memos, scheduling procedures, and evaluation protocols. This book is a volume in the Jossey-Bass Leadership Library in Education―a series designed to meet the demand for new ideas and insights about leadership in schools.